Rekonstruksi Destinasi Wisata Selo Bonang Desa Panduman Berbasis Geopark Argopuro Purba - Aprillianto, Bayu; Wahyuni, Nining Ika; Apriono, Markus; Fadah, Isti; Wilantari, Regina Niken; Pratama, Theodicy Kristian; Adhani, Brilian Farel; Agustriono, Aldi (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
Selo Bonang is a tourist destination in Panduman Village, Jember Regency, which has iconic potential, namely a stone site that produces notes, known as the "Singing Valley." This site has the potential to become the world's first natural stone studio. This village faces several problems, namely the low competency of Human Resources (HR) in optimizing tourism potential, as well as the lack of a clear concept and identity in the development of Selo Bonang. Apart from that, there is an asymmetry of information regarding the history of the founding of Selo Bonang. The objectives of this community service are: 1) increasing human resource competency, 2) assisting in formulating development ideas and concepts, 3) strengthening tourist identity to overcome the asymmetry of historical information in Selo Bonang, and 4) establishing a chat spot that displays Jember's urban views. This tourist location is on the slopes of Mount Argopuro and close to the Duplang Site, which is part of the ancient heritage. This shows the integration of the potential of ancient heritage into the development of tourism based on the Purba Argopuro Geopark. The approach used is community-based tourism and spatial and infrastructure planning, with a focus on developing human resources in preparation for tourism planning and management as well as good tourism skills. Implementation methods include training, Focus Group Discussions (FGD), and assistance to Selo Bonang managers and the surrounding community. The results of the activities include: 1) increasing the competence of tourism managers and the community around Selo Bonang, 2) optimizing potential through a Selo Bonang development roadmap based on the Argopuro Purba Geopark, 3) tourism identity in the form of a profile book, 4) building a photo spot called Selo Bonang Urbanscape. It is hoped that these development ideas and concepts can contribute to the independence of managers and surrounding communities to achieve Sustainable Development Goals (SDGs).